Self-concept of rural, urban and private teachers and academic performance of their students during the pandemic - Enrique Ibarra Aguirre; Pedro Acevedo Macías (Universidade Federal do Norte do Tocantins, 2021)
Its objective is to describe the self-concept of urban and rural public primary basic education teachers and private schools, as well as their links with the group grade point average of the students in their charge, during the COVID-19 pandemic. It is a quantitative, descriptive and cross-sectional work. A convenience sample made up of 115 teachers from the State of Sinaloa, Mexico; 88 (83.8%) are female (16.2%) and 17 male. The Form-5 Self-Concept Questionnaire was used. The emotional dimension presents lower scores, but with more decline in women. The 41-46 year-old age group expresses a multidimensional self-concept greater than the other groups. Teachers in urban public schools present higher self-concept means than those in rural schools and schools. Academic performance is highest in private schools, followed by urban and rural. There is an association between academic self-concept and academic performance, but it is not significant. The findings impel the educational system to provide psychological support to teachers, for their well-being in difficult times and experiences and to offer the best educational service, for the benefit of the educational achievement of the students.